DIVERSITY IN MAIN DISHES PREVENTS CHILDREN FROM COMPOSITE INDEX OF ANTHROPOMETRIC FAILURE (CIAF) - Welly Femelia; Sukarsi Rusti; Zainal Abidin (HUMAN CARE JOURNAL, 2019)
Background: Malnutrition that occurs in early period of life caused the vulnerable to diseases, cognitive disorder and failed to thrive. Failed to thrive decide from the result of anthropometric measurement. Failed to thrive happened when the result of measuring indicate a problem. If the problem showed in two or more index, it is called CIAF. In Indonesia one of two children had CIAF (51,4 %). Cities in Indonesia use only a single index of anthropometry so the data of CIAF is not available. Objective: the objective of the study was to find the association of food diversity with the incidence of CIAF. Method: cross – sectional design applied in this study with the number of sample were 267 children aged 2 – 5 years. Result: there were 23,6% children suffered from CIAF and generally consume the same type of food everyday. There was a significant association between diversity in main food consumption with the incidence of CIAF (p = 0,034). It means children who consume diversity main food everyday protected from CIAF compared to the children who eat the same main food each day (OR = 2). Conclusion: main food diversity prevents the children from CIAF. The mother expected to provide diversity source for the main dishes everyday (other than rice) such as bread or potato. For the health institutions, suggested to increase the education about the variaty of food processing towards so that the children could escape from the boredom.